Implementasi Modul Digital Berbasis Problem Based Learning (PBL) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran PAI di SD Negeri Jetis - Ipung Wistasari; Lovandri Dwanda Putra; Nonik Juhariah; Khalillah Sausan Rahmatullah; Firliyani Nurrahmabillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Education in the 21st century is expected to produce human resources equipped with competencies and skills that align with contemporary demands. Teachers play a pivotal role in integrating technology as a pedagogical tool through the use of digital-based teaching materials, methods, and media. This study aims to describe the implementation of a digital module grounded in Problem Based Learning (PBL) to enhance students’ critical thinking skills in Islamic Religious Education (IRE) at the elementary school level. Employing a descriptive qualitative approach, data were collected through interviews and subsequently analyzed systematically to ensure validity and reliability of findings. The results indicate that the application of digital modules based on PBL fosters students’ critical thinking abilities in IRE learning, while simultaneously serving as an innovative digital learning medium relevant to the challenges of the 21st century. The module’s implementation comprising video presentations, audio recordings, flipbooks, practice exercises, and integration into classroom activities proved effective as a pedagogical solution tailored to the characteristics of learning materials and the digital-native learning styles of contemporary students.